Understanding How to Form a Successful Social Entrepreneurship: Motivation Opportunity Ability Perspectives - Novita, Dian; Lia Febria Lina; Saifuddin, Muchammad (UPY Business and Management Journal (UMBJ), 2025)
Purpose: The presence of social entrepreneurship can serve as a compelling catalyst, motivating individuals to embrace entrepreneurship as a means to address local challenges and foster innovation. Methodology: This study uses a qualitative approach with an exploratory case study design. Data were collected through semi-structured interviews, direct observation, and internal document analysis. The interviewed participants were founder and orphanage children who were actively involved in entrepreneurial activities. Findings: Drawing upon the Motivation, Ability, and Opportunity (MOA) framework, the findings revealed that motivation stems from a strong social spirit and personal lifelong dreams. Opportunities arise from the unique concept of socio entrepreneur in orphanages and ease of obtaining funds, while abilities include social skills, leadership, financially independent and social capita). Originality: Research in the field of social entrepreneurship is also still limited. The primary objective was to delve deeper into the motivations of social entrepreneurs within orphanages and identify factors contributing to their success in fostering entrepreneurship Research limitations: The outcome resulting from entrepreneurship is a rich mindset, enjoying sharing, having my income, and increased motivation to become an entrepreneur. This finding needs further explanation and exploration using quantitative methods to better results.